2015
DOI: 10.1080/13825585.2015.1031723
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific differences of dualn-back training

Abstract: Age-related decline in executive functions can be decisive in performing everyday tasks autonomously. Working memory (WM) is closely related to executive functions, and training of WM has yielded evidence toward cognitive plasticity in older adults. The training effects often transfer to untrained tasks and functions. These effects have mostly been shown in processes such as WM and attention, whereas studies investigating transfer to executive functions have been scarce. We trained older adults aged 57-73 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 62 publications
2
22
1
Order By: Relevance
“…Their results demonstrated transfer from WM training to all aspects of executive function except coordination of concurrent performance, which the authors attributed to a “lack of commonalities” between the trained and target tasks (e.g., differences in the extent to which speeded processing was necessary for optimal performance). Salminen et al’s (2012) results reinforce the notion that transfer effects depend on specific cognitive processes shared by the WM training and target tasks (see also Persson et al, 2007 ; Karbach and Kray, 2009 ; Sprenger et al, 2013 ; Salminen et al, 2015 ).…”
Section: Introductionsupporting
confidence: 76%
“…Their results demonstrated transfer from WM training to all aspects of executive function except coordination of concurrent performance, which the authors attributed to a “lack of commonalities” between the trained and target tasks (e.g., differences in the extent to which speeded processing was necessary for optimal performance). Salminen et al’s (2012) results reinforce the notion that transfer effects depend on specific cognitive processes shared by the WM training and target tasks (see also Persson et al, 2007 ; Karbach and Kray, 2009 ; Sprenger et al, 2013 ; Salminen et al, 2015 ).…”
Section: Introductionsupporting
confidence: 76%
“…This could be interpreted as evidence that this type of training improved switching abilities and thus cognitive flexibility (Klingberg 2010). This later finding is inconsistent with other studies; these other studies showed no transfer from working memory updating training to the ability to switch between tasks (e.g., Salminen et al 2016a). However, it should also be noted that the switching demands in the TMT 2 (related to processing alternations between letters and digits) are much less pronounced (and of a somewhat different kind) than in other task switching paradigms (e.g., see Kiesel et al 2010, for a review), which makes it difficult to directly compare training effects across studies.…”
Section: Discussion Of the Present Findings And Relations To Other Trcontrasting
confidence: 56%
“…The aim of the present study is to verify whether N ‐back task performance improves during N ‐back training and EEG recording, and whether transfer effects to other (untrained) cognitive functions can be observed, such as spatial memory, attention, and fluid intelligence, in two different groups of healthy young and older subjects. Although mixed results have been reported (Clark, Lawlor‐Savage, & Goghari, ; Lawlor‐Savage & Goghari, ; Salminen, Frensch, Strobach, & Schubert, ; Stephenson, & Halpern, ), in light of the results obtained in previous studies for both near‐ (Li et al, ; Stephenson & Halpern, ) and far‐transfer effects (Jaeggi et al, ) in healthy young adults and near‐ (Heinzel et al, ; Stepankova et al, ) and far‐transfer effects (Borella et al, ; Heinzel et al, ) in healthy older adults, we hypothesize that improvements in the trained task and near‐ and far‐transfer effects are observed in both age‐groups, with greater gains in young compared to older adults. Besides behavioral responses, we will also record ERP responses as they have shown to reflect the time course of cognitive and sensory processes during cognitive task performance.…”
Section: Introductionmentioning
confidence: 96%